Pengaruh Pendidikan Kesehatan Dengan Metode Ceramah Dan Audiovisual Terhadap Pengetahuan Tentang Infeksi Menular Seksual Pada Remaja - Aditya Ramadhani; Meida Laely Ramadani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
ABSTRAK Keywords:Health education, lecture methods, audiovisual media, sexually transmitted infectionsObjective: To determine the effect of health education with lecture methods and audiovisual media on knowledge of sexually transmitted infections in adolescentsMethod:This article is a quantitative study using a quasy experimental design with a randomized pretest-posttest two group design approach with 94 respondents divided by 2. Data were analyzed by paired sample T test.Results: The results of the average pretest-posttest are audiovisual media before 12.68 after 15.26 and lecture method before 14.38 after 15.43. There is a difference between health education with audiovisual p value 0.001 while with lecture there is no influence p value 0.930.Conclusion: The results showed an increase in adolescent knowledge about sexually transmitted infections and the difference between health education with the lecture method and audiovisual media, as seen from the results of health education scores with the lecture method and audiovisual media were more effective audiovisual because of the presentation of interesting material and increased adolescent memory.